Analisis Terhadap Hukum Positif Dan Fiqih Pada Perkawinan Siri Dan Pengaruhnya Terhadap Kepemilikan Harta Kekayaan - Anggi Nur Nisa Tanjung; Wahyu Ziaulhaq (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
This article describes the analysis of positive law and fiqh on unregistered marriages and their effect on property ownership. The purpose of writing this article is to educate the public that the practice of unregistered marriage affects property ownership. The result of writing this article is that unregistered marriage has many negative effects, one of which is that it does not have legal force, so that it affects the rights of the wife and does not get legal guarantees. Likewise with property ownership, the wife does not get the property rights obtained after the unregistered marriage takes place, thus harming the wife. Therefore, as an Indonesian citizen who obeys the law, it is not allowed to carry out an unregistered marriage because it violates the applicable legal mechanism. The practice of marriage that is legally valid in fiqh and positive law is that the name has been recorded by the marriage registrar, namely the District Religious Affairs Office.